2019
DOI: 10.1159/000496484
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Associated Acute Kidney Injury in a Large Veteran Population

Abstract: Background: To determine the association of vancomycin with acute kidney injury (AKI) in relation to its serum concentration value and to examine the risk of AKI in patients treated with vancomycin when compared with a matched cohort of patients receiving non-glycopeptide antibiotics (linezolid/daptomycin). Methods: From a cohort of > 3 million US veterans with baseline estimated glomerular filtration rate ≥60 mL/min/1.73 m2, we identified 33,527 patients who received either intravenous vancomycin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
4
26
0
3
Order By: Relevance
“…This inding is of particular importance as it suggests that the association seen between high serum vancomycin trough levels and VA-AKI is not confounded by severity of sepsis and hemodynamic instability. A recent study has also shown similar indings [3].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This inding is of particular importance as it suggests that the association seen between high serum vancomycin trough levels and VA-AKI is not confounded by severity of sepsis and hemodynamic instability. A recent study has also shown similar indings [3].…”
Section: Discussionsupporting
confidence: 65%
“…Vancomycin is often used as a irst line empiric therapy for many moderate-to-severe gram-positive infections and has been associated with AKI [4]. Given the widespread use of vancomycin, there are reports of VA-AKI ranging between 5% to 40% [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum inhibitory concentration (MIC) of vancomycin for most sensitive bacteria is 0.1–2 μg ml -1 ( Bhongsatiern et al, 2015 ; Bruniera et al, 2015 ). Many of the adverse reactions of vancomycin such as bone marrow hematopoietic toxicity and nephrotoxicity are closely related to the blood concentration and area under the curve (AUC) of vancomycin ( Bruniera et al, 2015 ; Gyamlani et al, 2019 ). Pharmacokinetics, blood concentration, efficacy, and toxicity of vancomycin vary according to various factors including patient’s physiology, pathology, and combined medication ( Giuliano et al, 2010 ; Chu et al, 2016 ; Bakke et al, 2017 ; Hu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%